2015
DOI: 10.1128/jvi.03607-14
|View full text |Cite
|
Sign up to set email alerts
|

High Secretion of Interferons by Human Plasmacytoid Dendritic Cells upon Recognition of Middle East Respiratory Syndrome Coronavirus

Abstract: The Middle East respiratory syndrome coronavirus (MERS-CoV In 2012 a novel human betacoronavirus associated with severe respiratory disease emerged in Saudi Arabia (1). Due to its geographic distribution, this new virus was classified as Middle East respiratory syndrome coronavirus (MERS-CoV) (2). MERS-CoV is associated with high fatality rates (3, 4), and case numbers globally have increased to 909 laboratory-confirmed cases with 331 fatalities (as of 21 November 2014 [http://www.who.int/csr/don/ 21-november-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
103
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(106 citation statements)
references
References 63 publications
1
103
0
2
Order By: Relevance
“…MERS‐CoV has been reported to productively infect human DCs in vitro , which can also serve as a vector for viral dissemination within the body (Chu et al., ). However, human DCs can secrete interferons (IFNs) and then trigger a potent innate/adaptive response upon MERS‐CoV infection (Scheuplein et al., ). Thus, those DC‐like cells could interfere with viral replication by releasing cytokines, like type I IFNs, or delivering antigens to other immune cells at the time MERS‐CoV reaches this area (Scheuplein et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MERS‐CoV has been reported to productively infect human DCs in vitro , which can also serve as a vector for viral dissemination within the body (Chu et al., ). However, human DCs can secrete interferons (IFNs) and then trigger a potent innate/adaptive response upon MERS‐CoV infection (Scheuplein et al., ). Thus, those DC‐like cells could interfere with viral replication by releasing cytokines, like type I IFNs, or delivering antigens to other immune cells at the time MERS‐CoV reaches this area (Scheuplein et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…However, human DCs can secrete interferons (IFNs) and then trigger a potent innate/adaptive response upon MERS‐CoV infection (Scheuplein et al., ). Thus, those DC‐like cells could interfere with viral replication by releasing cytokines, like type I IFNs, or delivering antigens to other immune cells at the time MERS‐CoV reaches this area (Scheuplein et al., ). Future studies on this topic are therefore required to verify whether these cells are effectively DCs and if they are able to express DPP4 at the surface before infection.…”
Section: Discussionmentioning
confidence: 99%
“…Dromedary camels are also reported to be the reservoir of another major zoonotic diseasethe Middle East Respiratory Syndrome coronavirus (MERS-CoV) and as a direct source of infection to humans (Gossner et al, 2016;Wernery et al, 2017).Type I interferons play an important role in the host response against MERS-CoV. Interaction of the MERS-CoV with the human antigen-presenting cells (APCs) and dendritic cells significantly induce the expression of type I and III IFNs, particularly IFN-α (Scheuplein et al, 2015). IFN-α2b treatment along with ribavirin is effective in treating MERS-CoV (Falzarano et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…However, a previous study also showed increased levels of interferon-α in a patient who survived MERS-CoV infection but not in a person who died of MERS ( 7 ). Although MERS-CoV evades induction of innate immune responses by cell types, the virus elicits interferon responses in plasmacytoid dendritic cells in vitro ( 8 ). Levels of tumor necrosis factor-α, MIP-1α, MIP-1β, IL-10, and IL-1β did not increase in any of these specimens.…”
mentioning
confidence: 99%